Русловые процессы в бассейне верхней и средней Камы (Географический вестник=Geographical bulletin, 2017)
Изучены морфодинамические типы русел рек Камского бассейна. Установлено, что наибольшее распространение в нем получили реки с врезанным и широкопойменным руслом; преобладают сегментные излучины (46 %) и относительно прямолинейные участки русел (26 %). Выявлена относительно высокая встречаемость синусоидальных и прорванных излучин. Отмечено, что в последние десятилетия наблюдается упрощение конфигурации русел а также высокой становится вероятность смены общей направленности развития русловых процессов.CHANNEL PROCESSES IN BASIN UPPER AND MIDDLE KAMAStudying morphodynamic types channels the riversKamabasin has shown, that in it the rivers with incised and expanded floodplane channel use the greatest distribution. Segment bends (46 %) and rather rectilinear sites the channels (26 %) prevail. Occurrence of the sine wave and broken through bends is rather high. The concave coast of bends are washed away with a speed from first tens centimeters up to 10 m/years. Last decades simplification of a configuration the channels is observed. In conditions of a changing climate high there is a probability of change of the general orientation of development channel processes.